2001
DOI: 10.1016/s0167-6105(01)00074-5
|View full text |Cite
|
Sign up to set email alerts
|

A wind tunnel study of organised and turbulent air motions in urban street canyons

Abstract: High concentrations of car-exhaust gases in urban street canyons are typically associated with low wind velocities or situations when the wind blows perpendicular to the canyon axis. The latter flow configuration has been studied in a wind tunnel model of a street canyon. The mean flow and turbulence structure have both been investigated and comparisons have been carried out with results of full-scale flow measurements in urban street canyons. A qualitative similarity has been found between the results of atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
84
0
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(107 citation statements)
references
References 11 publications
9
84
0
10
Order By: Relevance
“…In a similar study, Rafailidis (1997) still observed pronounced peaks in Reynolds stress and turbulence intensity profiles above an array of idealized street canyons for particular roof shapes. Kastner-Klein et al (2001) analyzed mean flow and turbulence data measured in wind-tunnel models of idealized street canyons in comparison with data from corresponding field studies, and found qualitative similarity between wind-tunnel flow characteristics and their atmospheric counterparts. Cheng and Castro (2002) presented detailed mean flow and turbulence data inside and above idealized urban surfaces, which consisted of regularly spaced (packing density 25%) cubes and rectangular blocks.…”
Section: Introductionmentioning
confidence: 98%
“…In a similar study, Rafailidis (1997) still observed pronounced peaks in Reynolds stress and turbulence intensity profiles above an array of idealized street canyons for particular roof shapes. Kastner-Klein et al (2001) analyzed mean flow and turbulence data measured in wind-tunnel models of idealized street canyons in comparison with data from corresponding field studies, and found qualitative similarity between wind-tunnel flow characteristics and their atmospheric counterparts. Cheng and Castro (2002) presented detailed mean flow and turbulence data inside and above idealized urban surfaces, which consisted of regularly spaced (packing density 25%) cubes and rectangular blocks.…”
Section: Introductionmentioning
confidence: 98%
“…To better understand its complex nature, wind-tunnel or waterchannel experimental studies (e.g., Kastner-Klein et al 2001;Princevac et al 2010), numerical modeling studies (Letzel et al 2012;Park et al 2013), and field experimental studies (e.g., Brown et al 2004;Zajic et al 2011) have been performed extensively.…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies were thought to be caused by the difficulty in specifying reference parameters, such as the friction velocity, displacement height or roughness length. This problem has also been partly described by Kastner-Klein et al (2001). The geometry of the buildings and, in general, of the urban area also has a major influence on the production of turbulence inside and outside a canyon.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these studies, details of the exchange mechanisms, and the velocities and fluxes between a canyon and the flow above, are not well understood and stand in need of further research. Kastner-Klein et al (2001) underlined a common difficulty encountered in many studies. Observations from field measurements can rarely be compared with data from either wind tunnel or computational approaches.…”
Section: Introductionmentioning
confidence: 99%